COVID-19 and Cardiac Arrhythmias - Duckheim, Martin; Schreieck, Jürgen (Hämostaseologie, 2021)
Since the coronavirus disease (COVID-19) pandemic spread unrelentingly all over the world, millions of cases have been reported. Despite a high number of asymptomatic cases, the course of the disease can be serious or even fatal. The affection of the myocardium, called myocardial injury, is caused by multiple triggers. The occurrence of cardiac arrhythmias in COVID-19 patients with myocardial involvement and a critical course is common. In this review, potential mechanisms, incidence, and treatment options for cardiac arrhythmias in COVID-19 patients will be provided by performing a literature research in MESH database and the National Library of Medicine. Common cardiac arrhythmias in COVID-19 patients were sinus tachycardia, atrial fibrillation (AF), ventricular tachycardia (VT), ventricular fibrillation (VF), atrioventricular block, sinusoidal block or QTc prolongation. AF was the most common heart rhythm disorder. About 10% of COVID-19 patients develop new-onset AF and 23 to 33% showed recurrence of AF in patients with known AF. One retrospective trial revealed the incidence of VT or VF to be 5.9% in hospitalized patients. Both AF and VT are clearly associated with worse outcome. Several mechanisms such as hypoxia, myocarditis, myocardial ischemia, or abnormal host immune response, which induce cardiac arrhythmias, have been described. The effect of QT-prolonging drugs in inducing cardiac arrhythmias has become mitigated as these medications are no longer recommended. Acute management of cardiac arrhythmias in COVID-19 patients is affected by the reduction of exposure of health care personnel. More prospective data are desirable to better understand pathophysiology and consecutively adapt management.
Keywords: COVID-19; cardiac arrhythmia; sudden cardiac death; atrial fibrillation; ventricular tachycardia; SARS-CoV-2